Financial Inclusion and Poverty Alleviation in East Java: Evidence From SUSENAS 2023 With a Two-Stage Residual Inclusion (2SRI) Approach - Ahmad Syaifullah; Khusaini, Moh.; Fadli, Faishal (Wacana Journal of Social and Humanity Studies, 2025)
This research examines the impact of financial inclusion on household poverty status in East Java Province by analyzing microdata from the 2023 National Socioeconomic Survey (SUSENAS), with the household as the unit of analysis. The main objective of this study is to evaluate the extent to which access to and use of formal financial services can reduce the likelihood of households experiencing poverty. To address potential endogeneity in the financial inclusion variable, the Two-Stage Residual Inclusion (2SRI) method is used, with ownership of fixed assets such as land or houses (real estate) as an instrumental variable to strengthen causal identification.  The results show that financial inclusion significantly reduces households' probability of poverty. Specifically, access to digital financial services reduces the risk of poverty by 10.9%, and bank account ownership by 6.4%, while access to credit without adequate financial literacy actually increases the risk of poverty by 24.7%. The model successfully passes various diagnostic tests, including endogeneity (p < 0.01) and instrument relevance (first-stage F-statistic > 10), which strengthens the validity of the estimation results. Furthermore, the Average Marginal Effect (AME) analysis supports these findings, showing that digital financial services have the most significant negative marginal effect on poverty risk (?0.109), followed by account ownership (?0.064). In contrast, access to credit has a positive marginal effect (+0.247), indicating that unproductive credit use can increase household vulnerability. These findings underscore the importance of expanding access to inclusive and responsible financial services, particularly in rural and underserved areas. Improving public financial literacy and addressing spatial inequality are key to maximizing the poverty-reducing impact of financial inclusion. The study's findings provide relevant, evidence-based policy insights for designing more targeted, equitable, and contextualized poverty alleviation strategies in Indonesia. Keywords: Financial inclusion, Poverty alleviation, 2SRI, East Java, SUSENAS 2023